CVM-1118 (foslinanib), a 2-phenyl-4-quinolone derivative, promotes apoptosis and inhibits vasculogenic mimicry via targeting TRAP1 - Lifen Shen; Yen-Ling Chen; Chu-Chun Huang; Yu-Chiau Shyu; Yu-Chiau Shyu; Richard E. B. Seftor; Elisabeth A. Seftor; Mary J. C. Hendrix; Du-Shieng Chien; Yi-Wen Chu (Frontiers Media S.A., 2023)
CVM-1118 (foslinanib) is a phosphoric ester compound selected from 2-phenyl-4-quinolone derivatives. The NCI 60 cancer panel screening showed CVM-1125, the major active metabolite of CVM-1118, to exhibit growth inhibitory and cytotoxic effects at nanomolar range. CVM-1118 possesses multiple bioactivities, including inducing cellular apoptosis, cell cycle arrest at G2/M, as well as inhibiting vasculogenic mimicry (VM) formation. The TNF receptor associated protein 1 (TRAP1) was identified as the binding target of CVM-1125 using nematic protein organization technique (NPOT) interactome analysis. Further studies demonstrated CVM-1125 reduced the protein level of TRAP1 and impeded its downstream signaling by reduction of cellular succinate levels and destabilization of HIF-1α. The pharmacogenomic biomarkers associated with CVM-1118 were also examined by Whole Genome CRISPR Knock-Out Screening. Two hits (STK11 and NF2) were confirmed with higher sensitivity to the drug in cell knock-down experiments. Biological assays indicate that the mechanism of action of CVM-1118 is via targeting TRAP1 to induce mitochondrial apoptosis, suppress tumor cell growth, and inhibit vasculogenic mimicry formation. Most importantly, the loss-of-function mutations of STK11 and NF2 are potential biomarkers of CVM-1118 which can be applied in the selection of cancer patients for CVM-1118 treatment. CVM-1118 is currently in its Phase 2a clinical development.